Immunity to mumps virus in children population in Bulgaria - Stefka Krumova; Radostina Stefanova; Savina Stoitsova; Petia Genova-Kalou; Kremena Parmakova (Biotechnology & Biotechnological Equipment)
Mumps is an acute, contagious, viral vaccine-preventable disease caused by mumps virus (MuV). The measles, mumps, rubella (MMR) vaccine that is used in many countries is considered highly effective with decreased MuV incidence, but suboptimal MuV long-term immunity. This study assessed the MuV seropositivity and antibody titre among vaccinated children in Bulgaria to provide evidence for a better understanding of MuV circulation and immunity in Bulgaria. The samples from 734 immunized children (369 females and 365 males) aged 1 to 16, divided into four age groups (≥1, 2–6, 7–11, and 12–16) were tested. Qualitative and quantitative indirect enzyme-linked immunosorbent assay (Anti-Mumps IgG ELISA, Euroimmun, Germany) was performed to determine the mumps IgG antibody levels in sera. Among all participants, protective MuV immunity was identified in 93%. MuV IgG antibody positivity ranged between 87% in the age group between 1 and 2 years and 96% in the age group 12–16 years, but no statistically significant difference was found among age groups. At the same time, there was a statistically significant difference (p = 0.01) between seropositivity in male and female participants, with male participants having an overall seropositivity of 90% and female 95%. Among the antibody-positive samples, the quantitative measurements of median anti-MuV IgG concentrations showed that titres decreased with increasing age. A slightly waning immunity following vaccination was observed, but positivity remained high among vaccinated children over the years. Similar studies show that maintaining high immunity is crucial to prevent mumps outbreaks.